Estudo sobre sepse neonatal : avaliação dos praâmetros hematológicos e de subpopulações linfocitárias em recém-nascidos sépticos e não sépticos - Pitombeira, Alaíde da Silva (2006)
Neonatal sepsis is one of the most important cause of death of the newborn admitted to the Intensive Care Units; hence, the identification of the prognostic factors of this disease becomes very relevant in the follow up and evaluation of the patients. The aim of this study was to evaluate the hematological parameters and the lymphocyte subpopulations of the newborn with sepsis; in order to identify those parameters that may correlate with the onset of this neonatal disease. Twenty one newborns admitted to the ICU of the Albert Sabin Children’s Hospital, and a group of 10 healthy newborns from the Obstetric Center of the Angeline General and Maternity Hospital, were studied. In the two groups, red cells, hematocrit, hemoglobin, platelets, total and differential leukocytes, absolute and relative T and B cells; as also the blood PCR values in the septic newborn, were determined. In addition, NK, B, TCD4+ and TCD8+ cell numbers were evaluated by immunophenotyping, using their respective markers CD56, CD19, (CD3 + CD4) and (CD3 + CD8). The data were expressed as variation and mean ± SD, and analyzed by Student’s T test, at the significance level of p = 0.05. Significant differences were not observed between septic and non-septic newborn, in the mean values of the parameters: red cells, hematocrit, hemoglobin, platelets, total lymphocytes, and T, B, T CD4+, TCD8+ lymphocytes. Total leukocyte counts were elevated in septic newborns (18.080 ± 9.210/µL in septic patients, against 12.040 ± 3.980/µL in controls; the difference between the means significant, p = 0.0166); due, principally, to increase of circulating polymorphic neutrophils. PCR levels were elevated in newborns with fatal sepsis; as compared to those of septic newborns who responded to treatment (fatal sepsis: 38,00 ± 13,15 mg/L; non-fatal sepsis: 13,00 ± 8,83 mg/L – the differencea between the means highly significant, p < 0,01). The NK cells were highly significantly reduced in septic newborns (80 ± 80/µL; v 250 ± 220/µL dos controles; p = 0,0041). Of the septic cases, the mean NK values for those who responded to treatment was 32 ±20/µL; against 120 ± 80,90/µL for those with fatal sepsis. Both these values were below that of the control group; but the difference between the means of the two subgroups of the septics was significant (p = 0,0124). These results suggest that NK cells were reduced significantly in septic newborn; irrespective of their response to treatment, or not. However, the true significance of the oscillation of NK cell numbers in neonatal sepsis could not be evaluated in this study, because of the small numbers of septic newborns available for the subgroups under study. Investigations with much larger number of cases of septic newborns could better define the real role of NK cells in sepsis and its evolution to fatality.